Lietuvių ikitarybinės bibliografijos išliekamoji vertė - Žukas, Vladas (Knygotyra, 1976)
Bibliographical works of the past should be judged by three criteria: historical, theoretical and informational.The bibliographies must be evaluated from the historical point of view – their cultural and informative aspects should be estimated taking into account their historical conditions. For instance, some short lists and reviews of Lithuanian books of the 19th century (by K. Nezabitauskas, P. Köppen, L. Ivinskis) were important because they presented the first information about Lithuanian publications. They were significant historiographically as being the first reviews of Lithuanian literature. Some works of bibliography, which are no more rated bibliographically, nevertheless preserve their scholarly value, since they contain information about printing history and statistical data taken from archival documents lost by now.Theoretical significance should be attached to old bibliographies because they help to solve such problems as the formation of bibliography systems, the determination of the subject of national bibliographies, the functions of the bibliography, etc. For instance, the model of national Lithuanian bibliography was constructed early in the 19th century, later it was made more recise and was taken as the basis for the national bibliography which is now in preparation.The article also deals with the questions of bibliographical sources getting dated and the relationship between old and modern bibliographies. Lasting informational value is to be determined by the fullness of the index, the amount of the literature entered in the source (in a national bibliography), the significance and the scope of the subject (in a special bibliography), methods of presentation, displaying chronological, thematic and other aspects of literature.